Wide spectrum solar energy absorption based on germanium plated ZnO nanorod arrays: Energy band regulation, Finite element simulation, Super hydrophilicity, Photothermal conversion. (August 2022) - Zhang, Cai; Yi, Yingting; Yang, Hua; Yi, Zao; Chen, Xifang; Zhou, Zigang; Yi, Yougen; Li, Hailiang; Chen, Jing; Liu, Chao
Highlights: Simple process and low cost : ZnO nanorods were prepared by seed layer hydrothermal growth method. Germanium was deposited on the surface of the nanorods by magnetron sputtering. In addition, Ge can easily replace Zn in ZnO lattice structure to form ternary compound zinc orthogermanate (Zn2 GeO4 ). Improved band gap and absorption bandwidth: Germanium reduces the band gap of the material to 1.25 eV, in which the ternary compound Zn2 GeO4 also plays an important role. This makes the absorbent based on germanium plated ZnO nanorods have high absorptivity in the wavelength range (300-800 nm). High solar absorption rate: The LSPR effect on the surface of germanium deposited ZnO nanorods was analyzed by finite difference time domain (FDTD). FDTD results show that the visible light absorption effect of the material is greater than 91.8%. Meanwhile, the average spectral absorptivity of the absorbent based on germanium plated ZnO nanorods in the wavelength range (300-800 nm) is about 93.77%. Highlight thermal conversion and self-cleaning: Properly increasing the thickness of germanium is helpful to improve its conversion efficiency, the surface temperature of the best sample increased from room temperature (80 ° f) to 57°C (135 ° f) in 10 minutes. ZnO nanorods with special nanorod clusters combine the germanium film with the germanium particles on the surface, this makes the ZnO nanorod film gradually improve to a hydrophilic surface. ABSTRACT: Here, we propose a simple germanium plated ZnO local surface plasmon resonance (LSPR) nanostructure to achieve broadband high absorption of solar radiation visible spectrum. This enhanced absorption is mainly due to strong plasmon resonance and the improvement of material band gap. Germanium reduces the band gap of the material to 1.25 eV, in which the ternary compound Zn2 GeO4 also plays an important role. The LSPR effect on germanium deposited ZnO nanorods surface is analyzed by finite difference time domain (FDTD) method. FDTD results showed that the visible light absorption effect was greater than 91.8%. Meanwhile, the average spectral absorptivity of the absorber based on germanium plated ZnO nanorods in the wavelength range (300-800 nm) is about 93.77%. ZnO nanorods with special nanorod clusters combine the germanium film with the germanium particles on the surface, this makes the ZnO nanorod film gradually improve to a hydrophilic surface, so that the material has better photothermal conversion performance and stronger self-cleaning ability of water droplets. More importantly, it provides new insights into the mechanism and concept of visible spectrum solar absorber. Therefore, these characteristics and findings show that this study has broad application prospects in the fields related to solar energy collection and utilization. Graphical abstract: Here, we propose a simple germanium plated ZnO local surface plasmon resonance (LSPR) nanostructure to achieve broadband high absorption of solar radiation visible spectrum. This enhanced absorption is mainly due to strong plasma resonance and the improvement of material band gap. Germanium reduces the band gap of the material to 1.25 eV, in which the ternary compound Zn2 GeO4 also plays an important role. The LSPR effect on germanium deposited ZnO nanorods surface is analyzed by finite difference time domain (FDTD) method. FDTD results showed that the visible light absorption effect was greater than 91.8%. Meanwhile, the average spectral absorptivity of the absorber based on germanium plated ZnO nanorods in the wavelength range (300-800 nm) is about 93.77%. ZnO nanorods with special nanorod clusters combine the germanium film with the germanium particles on the surface, this makes the ZnO nanorod film gradually improve to a hydrophilic surface, so that the material has better photothermal conversion performance and stronger self-cleaning ability of water droplets. More importantly, it provides new insights into the mechanism and concept of visible spectrum solar absorber. Therefore, these characteristics and findings show that this study has broad application prospects in the fields related to solar energy collection and utilization. Image, graphical abstract